Pola Pengajian Kultural Ma’iyah Jamparing Asih di Bandung 2015-2018 - Alamsyah, Akbar Nur; Hasbullah, Moefllich (Historia Madania: Jurnal Ilmu Sejarah, 2020)
The Islamization in Indonesia since the 7th century has also involved the transformation of Islamic religious knowledge, also called pengajian (Islamic learning). The study in its development is divided into two types; First, non-formal Quranic recitation such as Quranic recitation at home, langgar and mosque. Secondly, formal Islamic learning is institutionalized like in a pesantren. Islamic boarding schools continue the tradition of formal learning while non-formal recitation has developed since the beginning of Islamization in the 7th century and has still lived in various forms. Non-formal learning because of its egalitarian and flexible nature so that there are no specific ties which are more attractive to many people to attend the recitation. This study aims to determine how the history, methods and study patterns used by Maiyah Jamparing Asih. The method used in this study is the historical research method in four stages such as heuristics, criticism, interpretation and historiography. The results of this study show that the Islamic learning of Maiyah Jamparing Asih was established in November 2015 by four people namely Wawan, Mufti, Andityas and Nissa which were approved by Cak Nun and Sheikh Kamba at his home in Jakarta. The learning pattern or method used by Maiyah Jamparing Asih in 2015 and 2016 almost entirely uses the general learning pattern, then in 2017 used the way of interpreting pattern of the Quran and in 2018 used the general learning pattern, and the recitation method used in 2015 and 2016 uses the lecture method, then in 2017 and 2018 it used the mudzakarah method.